PSOL - Relação da origem no desenvolvimento de sua organização, participação eleitoral e atuação parlamentar - Oliveira, Heythor Santana de (Universidade Federal de São Carlos, 2017)
The present dissertation aims to analyze the relationship between the organizational structure of the Partido do Socialismo e Liberdade (PSOL) and its characteristics. It starts from the premise that the origin of the party focuses directly on the format and organizational aspects that will build it. It seeks to identify the influence of genetic elements of the PSOL, which is born of a kind of internal rupture of Partido dos Trabalhadores (PT) parliamentarians, both in its development and in its political orientation. The específical hypothesis that there is a concentration of power in the party (parliamentary) and organizational arena of the party, in which the elective parliamentarians decide by the caption. Complements the organizational analysis complements the examination of the performance levels of the PSOL and the identification of ideological elements in its parliamentary action with the objective of exploring aspects originating from the party in its development.
Keywords: Partido político; PSOL; Origem partidária; Organização partidária; Political party; Party source; Party organization; CIENCIAS HUMANAS::CIENCIA POLITICA